Increased functional connectivity between the right temporo-parietal junction and the temporal poles in migraine without aura. (11th October 2018) - Lisicki, Marco; D'Ostilio, Kevin; Coppola, Gianluca; de Noordhout, Alain Maertens; Parisi, Vincenzo; Schoenen, Jean; Magis, Delphine
Rather than a localized alteration, increased visual reactivity in migraine patients seems to result from a complex interaction between several brain structures, mostly involving the ventral attention network. The hub of this network is the right temporo-parietal junction. In this report, complementing our previous findings, we describe the differences in seed-to-voxel resting-state functional connectivity seeded in the right temporo-parietal junction (right angular gyrus) between migraine patients and healthy controls. Resting-state functional MRIs of episodic migraine without aura patients in the interictal period ( n = 19) and matched healthy controls ( n = 19) were analysed. With the seed placed in the right temporo-parietal junction (right angular gyrus), seed-to-voxel connectivity was compared between groups. Electrophysiological, voxel-based morphometry (both groups) and specific region of interest (ROI)-to-ROI functional connectivity (migraine patients) data have already been published. Migraine patients showed a higher positive interaction between the right temporo-parietal junction and both temporal poles and a higher negative interaction between this same region and bilateral areas of the visual cortex. On the basis of our results, and because of their established properties as multisensory integration hubs, it is likely that the right temporo-parietal junction and both temporal poles are involved in the altered processing of sensory stimulus commonly observed in migraine patients. Therefore, more attention should be paid to these regions for migraine research in the future.